1986
DOI: 10.1128/aac.30.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two beta-lactamase-producing strains of Streptococcus faecalis

Abstract: A second strain of enterococcus (PA) producing beta-lactamase (Bla+ phenotype) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 17 publications
1
77
2
Order By: Relevance
“…3A and Table 1). The earliest isolate of this clone, HH-22, the first known Bla ϩ isolate of E. faecalis, is a multidrug-resistant urine isolate recovered in Texas in 1981 (18); the blaZ gene of this strain is located on a plasmid that also harbors a gene for high-level gentamicin resistance (HL-Gm r ) (16). Other members of this clone (which represents the majority of known Bla ϩ isolates) were subsequently found in five states of North America (20), including a large, prolonged outbreak in a Virginia hospital (33,40) and a hospital outbreak that included five bloodstream infections in North Carolina (13).…”
Section: Vol 187 2005 Evolution Of An E Faecalis Clonal Complex Anmentioning
confidence: 99%
“…3A and Table 1). The earliest isolate of this clone, HH-22, the first known Bla ϩ isolate of E. faecalis, is a multidrug-resistant urine isolate recovered in Texas in 1981 (18); the blaZ gene of this strain is located on a plasmid that also harbors a gene for high-level gentamicin resistance (HL-Gm r ) (16). Other members of this clone (which represents the majority of known Bla ϩ isolates) were subsequently found in five states of North America (20), including a large, prolonged outbreak in a Virginia hospital (33,40) and a hospital outbreak that included five bloodstream infections in North Carolina (13).…”
Section: Vol 187 2005 Evolution Of An E Faecalis Clonal Complex Anmentioning
confidence: 99%
“…Although the gene responsible for enterococcal ,-lactamase production is homologous with that found in Staphylococcus aureus, its phenotypic expression differs in that enterococcal P-lactamase is produced constitutively, is not excreted into the medium, and has only a minimal effect on the penicillin MIC at standard inoculum sizes (16). Genetic studies on five strains previously described have revealed the presence of the 1-lactamase genes on conjugative plasmids in close association with genes encoding enzymes conferring highlevel resistance to gentamicin (16,19,20).…”
mentioning
confidence: 99%
“…This strain also carried high-level resistance to all aminoglycosides. It is not surprising to find both penicillinase production and gentamicin resistance in the same bacterium, since both can be encoded on transferrable plasmids (42,43). Although penicillinase-producing enterococci appear to be rare, a few other strains have been isolated (24,45,46).…”
Section: Beta-lactam Resistancementioning
confidence: 99%
“…In recent years, however, increasing numbers of enterococcal isolates have acquired high-level resistance to the aminoglycosides (2,4,19,20,23,65). Enterococci for which MICs are above clinically achievable levels of the penicillins and vancomycin in serum have also been reported (19,31,42,43,57,59). Serious infections with these multiple-drug-resistant strains may not be curable with the traditional therapy.…”
Section: Introductionmentioning
confidence: 99%